Charakter doświadczanej edukacji artystycznej a miejsce sztuki w osobistym systemie wartości młodzieży = The nature of the experienced artistic education and a place of art in the personal value system of youth - Ferenz, Krystyna (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
Artistic education, as a component of a wider process of entering the culture by a human, has social and individual dimensions. In social dimension it is an organized process of preparing individuals to consciously participate in the cultural life. In the dimension of the individual, however, it can fulfil in the development of personality, giving a chance to mature choices in the local, regional and global culture.
Keywords: kultura; człowiek kulturalny; wrażliwość estetyczna; edukacja artystyczna; edukacja "do sztuki"; edukacja "przez sztukę"; culture; cultural man; aesthetic awareness; artistic education; education "towards art"; education "through art"